Review of Insulin Therapy In Type 2 Diabetes Mellitus Ambulatory Patients - Budi Suprapti; Nia Widyasari; Mahardian Rahmadi; Cahyo Wibisono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
The purposes of this study were to review utilization of insulin therapy in type 2 diabetes mellitus out patients and identify its drug related problems. The data were collected cross-sectionally with purposive sampling method in the period March 2016 until May 2016 in Outpatient Clinic Universitas Airlangga Teaching Hospital Surabaya. The results of 240 patients showed that insulin was used as monotherapy insulin in 2,9% patients; combination 1 insulin & 1-4 OAD in 31,3%; basal bolus therapy 27,9%; combination basal−bolus therapy & 1-3 OAD 43,9%. Based on blood glucose target achievement, only 20,8% of patients achieve the target, 75,1% failed to achieve the target and 4,1% suffered from hypoglycemia. Drug related problems identified adverse drug reaction of antidiabetic therapy such as hypoglycemia (6.7%), nausea (3.8%), bloating (1.3%), increase of flatulency (2.9%) and inappropriate combination (0,4%). In conclusion insulin therapy was complicated and individually, most of the patients still did not reach the target and there was potential drug related problem in this patients group. So that caring from solid inter-professional health collaboration is needed